A Comparative Assessment of Spalart-Shur Rotation/Curvature Correction in RANS Simulations in a Centrifugal Pump Impeller. (30th September 2014) - Tao, Ran; Xiao, Ruofu; Yang, Wei; Wang, Fujun
Abstract : RANS simulation is widely used in the flow prediction of centrifugal pumps. Influenced by impeller rotation and streamline curvature, the eddy viscosity models with turbulence isotropy assumption are not accurate enough. In this study, Spalart-Shur rotation/curvature correction was applied on the SST k -ω turbulence model. The comparative assessment of the correction was proceeded in the simulations of a centrifugal pump impeller. CFD results were compared with existing PIV and LDV data under the design and low flow rate off-design conditions. Results show the improvements of the simulation especially in the situation that turbulence strongly produced due to undesirable flow structures. Under the design condition, more reasonable turbulence kinetic energy contour was captured after correction. Under the low flow rate off-design condition, the prediction of turbulence kinetic energy and velocity distributions became much more accurate when using the corrected model. So, the rotation/curvature correction was proved effective in this study. And, it is also proved acceptable and recommended to use in the engineering simulations of centrifugal pump impellers.